EFEKTIVITAS FUEL OIL HEATER PADA PEMBANGKIT LISTRIK TENAGA UAP - Hatib, Rustan (Jurnal MEKANIKAL, 2012)
Fuel Oil Heater in Steam Power Plant (PLTU) at Tello Makassar, a heat exchanger type of heater that serves to heat the oil residue by using steam heat generated in the boiler. This study aimed to determine the effectiveness of water vapor to reduce the viscosity of oil residue that can be used as fuel by using fuel oil heater. Measurements were performed immediately when the temperature and pressure of water vapor and residual oil at the input and output unchanged (constant) for 1 hour. The results showed that the effectiveness is influenced by the amount of heat absorbed by the residual oil by 1726.083 W and the amount of heat released by the steam that is 1764.988 W with a value of 68.7% effectiveness.